Challenges and Prospects of Sustainable Livelihoods among Marginal Communities in rural areas of Jangal Mabal, West Bangal : - Chatterjee, Babita (IIT(BHU) Varanasi, 2026)
Abstract is available in the attachment.
Keywords: Humanistic Studies